2021
DOI: 10.3390/toxins13100732
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Heme Oxygenase-1 on Liver Injury Caused by DON-Induced Oxidative Stress and Cytotoxicity

Abstract: Deoxynivalenol (DON) is a kind of Fusarium toxin that can cause a variety of toxic effects. Oxidative stress and DNA damage play a critical role in the toxicity of DON. However, previous studies focused more on acute toxicity in vivo/vitro models and lacked subchronic toxicity study in vivo. The potentially harmful effect of DON given at doses comparable to the daily human consumption in target organs, especially the liver, which is the main detoxification organ of DON, is also still not fully understood. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Previous studies have reported that SelS overexpression mitigates OTA-induced cytotoxicity and apoptosis [21]. In addition, overexpression of HO-1 reduces the DON-induced ROS and DNA damage by maintaining DNA repair, antioxidant activity, and autophagy [22]. In this study, we observed that ISLR2 overexpression significantly increased the cell viability and reduced the ROS levels of cells exposed to ZEN, indicating the potential of ISLR2 as a molecular target for controlling ZEN-induced toxicity.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have reported that SelS overexpression mitigates OTA-induced cytotoxicity and apoptosis [21]. In addition, overexpression of HO-1 reduces the DON-induced ROS and DNA damage by maintaining DNA repair, antioxidant activity, and autophagy [22]. In this study, we observed that ISLR2 overexpression significantly increased the cell viability and reduced the ROS levels of cells exposed to ZEN, indicating the potential of ISLR2 as a molecular target for controlling ZEN-induced toxicity.…”
Section: Discussionsupporting
confidence: 66%
“…Mac-CF MDM exhibited down-regulation of Prdx1 , 5 , and 6 that encode peroxiredoxins for the metabolism of hydrogen peroxide, and down-regulation of the Heme oxygenase-1 gene Hmox1 ( Figures 6H, I ). HMOX expression has been previously found to be important in response to ROS and ROS-induced DNA damage ( 75 , 76 ). Peroxiredoxins are known to be important for the metabolism of hydrogen peroxide ( 77 , 78 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is a secondary metabolite toxin mainly produced by Fusarium graminearum and Fusarium flavus . DON contamination affects multiple organs of mammalians, including disruption of intestinal barrier integrity, destruction of antioxidant/oxidative balance, and alternation of the immune response. , As the metabolic hub of the body, the liver plays a critical role in protein synthesis, lipid metabolism, bile synthesis, and detoxification of harmful substances produced by internal metabolism or external factors. , Recent studies have underscored the liver as one of most targeted organs for DON. , Therefore, more attention should be devoted to the hepatotoxicity caused by DON.…”
Section: Introductionmentioning
confidence: 99%